Local identity construction analysis in Sopron - Ferenc, Balázs (Studia Mundi – Economica, 2018)
Due to the external and internal migration processes in the recent years, Sopron and its regionhave become a „gateway” city in two directions between Austria and Hungary. This processhas an impact on the population of the city and its spatial structure and the everyday life of thecitizens. According to this research, it is necessary to examine how can the incoming connectionto the city is formed in the local identity of the population of Sopron, as the city of "loyalty andfreedom".